Examining the Relationships Among Concealment Tendencies, Illness Attitudes, Belief in a Just World, and Cognitive Flexibility - Cha, Kyung Hwan; Jin, Hua; Ha, Jung Hee; Jue, Juliet (Frontiers in Psychology, 2021)
The purpose of this study was to verify the relationships among concealment tendencies, illness attitudes, belief in a just world, and cognitive flexibility. Based on prior studies, we assumed that cognitive flexibility mediates the concealment tendencies affecting illness attitudes and belief in a just world. To better understand their relationship, we collected data from two Asian countries with different cultures. The participants were 418 Korean and 400 Chinese adults. We conducted correlational analysis, structural equation modeling, and verification of mediating effects. We found that cognitive flexibility–control factor fully mediated the relationship between concealment tendencies and illness attitudes for Korean participants and partially mediated the relationship for Chinese participants. The relationship between concealment tendencies and cognitive flexibility–alternatives factor differed across participants’ country of origin. For Chinese participants, cognitive flexibility–alternatives fully mediated the relationship between concealment tendencies and belief in a just world. These differences might stem from the countries’ different social systems, values, and attitudes. Finally, we discuss this study’s implications and limitations.